Accumulation of lead and copper in Rhizophora apiculata from Setiu mangrove forest, Terengganu, Malaysia - Yunus, Kamaruzzaman; Ong, Meng Chuan; Khan Chowdhury, Ahmed Jalal; Saad, Shahbudin; Omar, Muhammad Nor (Triveni Enterprises, Lucknow (India), 2009)
The accumulative partitioning of Pb and Cu in the Rhizophora apiculata was studied randomly in the Setiu mangrove forest, Terengganu. Samples of leaves, barks and roots were collected randomly from the selected studied species. Sediments between the roots of the sampled mangrove plants were also collected. The results from analysis for Rhizophora apiculata shows that the concentration of Pb and Cu were accumulated higher in root tissue compared to bark and leaf tissue but lower than surrounding sediment level. The average concentration of Cu for Rhizophora apiculata in leaf, bark, root and sediment was 2.73, 3.94, 5.21 and 9.42 mg I(-1), respectively. Meanwhile, the average concentration of Pb in leaf, bark, root and sediment was 1.43, 1.38, 2.05 and 11.66 mg l(-1), respectively. Results of concentration factors (CF) show that the overall the concentration of Pb and Cu were accumulated much higher in roots system of Rhizophora apiculata.